Math, asked by vaibhavmanish2007, 3 months ago

please answer
help me​

Attachments:

Answers

Answered by syedkamranmehdi14feb
1

Answer:

3

Step-by-step explanation:

 (x+\frac{1}{x}) ^{2} = x^{2} +\frac{1}{x}^{2}+2

      (x+\frac{1}{x}) ^{2} = 7+2

      (x+\frac{1}{x})^{2}  =9

      x+\frac{1}{x} =3

       

Answered by jackiemehra20
0

2)

(7x+ 1/2 ) ( 7x− 1/2 ) = 49x^2 − b

b⇒49x^2 − 4/1 = 49x^2 b

(∵ (a−b) (a+b) = a^2 b^2)

2)⇒b= 4/1

1Option C is correct.

Attachments:
Similar questions